THE EFFECTIVENESS OF USING PICTURE TO IMPROVE SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMP NEGERI 1 KEFAMENANU - Fransiska Densiana Luruk; Merlin Helentina Napitupulu (Datokarama English Education Journal, 2022)
Language is a human and non-instinctive method of communicating idea, feeling and desires by means of a system of sounds and sounds symbols. Speaking is a number of impossible from must be selected. Picture is visual representation (of in object or scene or person or abstraction). This study is aim to know whether there is an effect of using picture to improve the speaking ability of SMP Negeri 1 Kefamenanu. The method used to conduct this study is descriptive quantitate method. There were 20 students class VIII in the second grade students of junior high school as the sample of this study. The result of the formula above, it is done through the following procedure check the t-score by using 1 level of significance states in the low of one tailed test. One tailed test used instantly of two tailed is the tendency of the writer in order to match with the result of the two groups. Thus, in accordance the result of the data analysis in this study concludes18 students have got score good 2 students got enough level. Based on the conclusion of data analysis the writer would like to give suggestion for the teacher and the students to pay attention more of the studying about speaking. Confronting with the large class teacher is expected to use a good method particularly communicative method that can help the students to be virtually independent for the spoken language.